Comorbidity and Health Condition - the Necessity for Integrated Care - Andreea Silvana Szalontay; Gabriela Chele; Corina Dima-Cozma; Sebastian Cozma; Ana Maria Burlea; Roxana Chirita (Romanian Society of Oral Rehabilitation, 2012)
Comorbidity has become a global health problem, a phenomenon which equally affects developing and developed countries. Comorbidity is associated with an increase of morbidity, mortality, has a strong impact on economy and is multidimensional in the frame of mental health and beyond. Management of comorbidity requires an integrated approach; community related and also focused on person, who takes into account medical, psychiatric and contextual factors.